Evaluasi Kepatuhan Pengobatan Menggunakan Google Form Pasien Pneumonia di Wilayah Kota Pontianak - Robby Najini; Shoma Rizkifani; M. Akib Yuswar; Yeni Utari Ningsih; Ade Ferdinan (State University of Gorontalo, 2023)
Pneumonia is an acute infection with the first line of treatment is antibiotics, so it is necessary to study patient adherence in undergoing treatment using the Medication Adherence Rating Scale (MARS) questionnaire through the Google Form. This study aims to determine the percentage of characteristic descriptions including age, gender, and treatment regimen, know the percentage level of patient adherence in undergoing treatment, as well as knowing the significant difference between monotherapy and combination therapy groups on treatment adherence to pneumonia patients under five in Pontianak City. The method used is an observational method with a cross sectional research design that is analytic. The data was collected by filling out the MARS questionnaire through the Google Form and the data were analyzed using the Chi-Square test method. The results showed that patients aged 4 years (56.1%), male patients (73.7%), monotherapy (70.2%), and high adherence (80.7%). The results of the Chi-Square test showed that there was no significant difference between the monotherapy and combination therapy groups on compliance with pneumonia patients, with values (RR = 0.354; 95% CI = 0.125-1.004). The conclusion of this study the use of Google Form as a survey medium is the percentage of pneumonia sufferers is greater in patients aged 4 years, male, the most commonly prescribed therapy regimen is monotherapy, and patient adherence falls into the high adherence category. There was no significant difference between monotherapy and combination therapy groups on compliance with pneumonia patients in Pontianak City.